An equation-based method for fully coupled analyses of floating offshore wind turbine based on Modelica. (1st February 2023) - Zhu, Yuanyao; Hu, Chao; Ma, Yong; Xie, Guangci; Yao, Zhi
Abstract: This paper presents a fully coupled aero-hydro-servo-elastic method to simulate floating offshore wind turbines (FOWT) based on Modelica language and AeroDyn co-simulations. The main features of this method are as follows. (1) The features of Modelica language (equation-based, object-oriented, and hierarchy structure) afford extreme flexibility and efficiency in the modeling process, and wind turbine structures or theoretical methods can be easily upgraded or replaced. (2) AeroDyn, a relatively precise aerodynamic load calculation module, is integrated into the system; thus, the model is more accurate than the previous Modelica library in calculating the responses of FOWTs. First, this paper introduces the theory of the proposed model in Modelica and AeroDyn module to calculate offshore FOWT response. Second, the implementation method for Modelica with AeroDyn is introduced. A dynamic link library (DLL) is programmed as the channel for exchanging data, and a controller to coordinate the stepping relationship between Modelica and AeroDyn is established. Third, code-to-code comparisons are performed based on International Energy Agency (IEA) Wind Task 23 Subtask 2. The results show excellent agreements between the proposed method and FAST in predicting dynamic responses of the rotor, tower, platform, and mooring system under both steady and turbulent winds combined with wave conditions. Finally, a case about high altitude work is carried out to demonstrate the flexibility of modeling processes. A single pendulum model constrained at the bottom is used to model the motion of the worker at a high altitude, coupled to the motion of a FOWT. The results show that the motion along the Y-axis is effectively suppressed as the damping force at the bottom increases, while the suppression is less pronounced on the X-axis. This method comprising the structure properties of blade and time domain potential flow hydrodynamic loads is more complete than the previous method using Modelica language to construct the fully coupled FOWT simulation model. Besides, it provides a more flexible modeling and simulation tool for some engineering practices, such as FOWT combined with fish cages, and FOWT operation and maintenance. Highlights: A fully coupled dynamics model is established by Modelica language and AeroDyn module. A code to code comparison with the IEC benchmark model verifies the feasibility of the proposed method. The shared memory is programmed to account for the aero-hydro-mooring coupling effects. The method can construct the model of the new FOWT concept with complex geometry or multi-rotor turbines. The method shows good flexibility and scalability for unconventional load cases modeling of FOWT.